Regional Incentives and Patient Cross-Border Mobility: Evidence from the Italian Experience - Elenka Brenna; Federico Spandonaro (Kerman University of Medical Sciences, 2015)
Background In recent years, accreditation of private hospitals followed by decentralisation of the Italian National Health Service (NHS) into 21 regional health systems has provided a good empirical ground for investigating the Tiebout principle of "voting with their feet". We examine the infra-regional trade-off between greater patient choice (due to an increase in hospital services supply) and financial equilibrium, and we relate it to the significant phenomenon of Cross-Border Mobility (CBM) between Italian regions. Focusing on the rules supervising the financial agreements between regional authorities and providers of hospital care, we find incentives for private accredited providers in attracting patient inflows. Methods The analysis is undertaken from an institutional, regulatory and empirical perspective. We select a sample of five regions with higher positive CBM balance and we examine regional regulations governing the contractual agreements between purchasers and providers of hospital care. According to this sample, we provide a statistical analysis of CBM and apply a Regional Attraction Ability Index (RAAI), aimed at testing patient preferences for private/public accredited providers. Results We find that this index is systematically higher for private providers, both in the case of distance/boundary patients and of excellence/general hospitals. Conclusion Conclusions address both financial issues regarding the coverage of regional healthcare systems and equity issues on patient healthcare access. They also raise concerns on the new European Union (EU) directive inherent to patient mobility across Europe.